2009
DOI: 10.1063/1.3071196
|View full text |Cite
|
Sign up to set email alerts
|

How far can a rubber molecule stretch before breaking? Ab initio study of tensile elasticity and failure in single-molecule polyisoprene and polybutadiene

Abstract: We present ab initio calculations of the internal C-C bond dissociation curve for single molecules of (cis-1,4) polyisoprene and polybutadiene. We define "bond rupture" as that point on the reaction coordinate where the unrestricted Kohn-Sham, or diradical, solution falls below the restricted, or closed-shell, solution. Using this definition, we find that rupture occurs at a tensile force of 6.8 nN for polyisoprene and 7.2 nN for polybutadiene. Their respective rupture strains are 45% and 42%. Our calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 22 publications
0
29
0
1
Order By: Relevance
“…It is based on previous ab initio and MD studies of polyisoprene molecules that have established that: (1) local molecular kinks, composed of a few isoprene units, can act as entropic springs 19 and (2) that there is a purely enthalpic elastic force associated with stretching a chain beyond its nominal contour length. 18 We presented two new chain force extension models to treat low and moderate strains along the chain contour (entropic regimes Ia and Ib) and combined them with the enthalpic force extension model, regime II. Both the low and moderate strain models assume that the network chains are constrained by tubes in the surrounding melt and that the intra-node forces are a consequence of the tensions along the connected chain contours.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is based on previous ab initio and MD studies of polyisoprene molecules that have established that: (1) local molecular kinks, composed of a few isoprene units, can act as entropic springs 19 and (2) that there is a purely enthalpic elastic force associated with stretching a chain beyond its nominal contour length. 18 We presented two new chain force extension models to treat low and moderate strains along the chain contour (entropic regimes Ia and Ib) and combined them with the enthalpic force extension model, regime II. Both the low and moderate strain models assume that the network chains are constrained by tubes in the surrounding melt and that the intra-node forces are a consequence of the tensions along the connected chain contours.…”
Section: Discussionmentioning
confidence: 99%
“…Our ansatz is that the force extension curve for polyisoprene molecules mimics this behavior; i.e., there are also three distinct extension regions for chain stretching. For two of these regions, MD and ab initio simulations 18,19 have provided quantitative predictions for the relevant chain forces, albeit for isolated chains. The simulations showed that isoprene units have 18 unique rotameric states and those with shorter end-to-end distances tend to be ∼1 kcal/mole higher in energy than the more extended conformations.…”
Section: Chain Extension Force Modelsmentioning
confidence: 98%
See 3 more Smart Citations